Stabilizing two-dimensional quantum scars by deformation and synchronization - A. A. Michailidis; C. J. Turner; Z. Papić; D. A. Abanin; M. Serbyn (Physical Review Research, 2020)
Relaxation to a thermal state is the inevitable fate of nonequilibrium interacting quantum systems without special conservation laws. While thermalization in one-dimensional systems can often be suppressed by integrability mechanisms, in two spatial dimensions thermalization is expected to be far more effective due to the increased phase space. In this work we propose a general framework for escaping or delaying the emergence of the thermal state in two-dimensional arrays of Rydberg atoms via the mechanism of quantum scars, i.e., initial states that fail to thermalize. The suppression of thermalization is achieved in two complementary ways: by adding local perturbations or by adjusting the driving Rabi frequency according to the local connectivity of the lattice. We demonstrate that these mechanisms allow us to realize robust quantum scars in various two-dimensional lattices, including decorated lattices with nonconstant connectivity. In particular, we show that a small decrease of the Rabi frequency at the corners of the lattice is crucial for mitigating the strong boundary effects in two-dimensional systems. Our results identify synchronization as an important tool for future experiments on two-dimensional quantum scars.